PERLUASAN MAKNA ZINA DALAM PASAL 417 RANCANGAN KUHP INDONESIA - Mochamad Ramdhan Pratama (Res Justitia : Jurnal Ilmu Hukum, 2022)
The Criminal Code of Dutch colonial heritage needs to be updated because Indonesia and the Netherlands have different characters and cultures. The discourse of overhaul, reform, revision, and even reform has become a long debate by criminal law experts to conform to the values of Indonesian society. The purpose of this study is to find out the Basic Determination of policies on the expansion of adultery and the values protected by the expansion of the Meaning of Zina in Article 417 of the Criminal Law Bill. This research is descriptive with normative juridical research types, using legal approaches and policy approaches. Data are collected through the study of literature, then analyzed qualitatively. This study shows that the basic determination of the policy of expanding adultery in Article 417 of the Criminal Law Bill is based on the perspective of criminal policy, the formulation of adultery in Article 284 of the Criminal Code is a problematic policy because the delik formula only criminalizes perpetrators who have been the same or one of them has been bound by marriage and does not criminalize those who are equally single. Meanwhile, the results of the second study show that the values protected by the expansion of the meaning of adultery in Article 417 of the Criminal Code are religious values, as well as moral values that are closely related to religion and the values of the Indonesian nation derived from Pancasila